A model for the prediction of olefin production thermal cracking of light hydrocarbons (2012)
Abstract. Thermal cracking of light hydrocarbons is the main route for the production of ethylene and propylene. Associated with cracking there is undesirable coke deposition on the walls of the reactor up to a point in which pressure drop and reduction on heat transfer efficiency are so high that furnace maintenance stops are mandatory. Predictions of diameter reduction because of coke deposition for two different raw materials (ethane and 50% ethane/propane mixture) were conducted with a pyrolysis reactor model developed to this aim. The cracking reactor was modeled as a tubular, one-dimensional reactor. After a careful evaluation of the kinetic mechanisms available in the literature for hydrocarbon pyrolysis, the mechanism that yielded results that were closer to those expected for ethane conversion in an industrial furnace was selected. A mechanism for coke formation, that has as input the species concentrations predicted by the gas phase mechanism, was proposed. The solid phase mechanism considers the most important precursors (benzene and acetylene) for the formation of carbonaceous materials (such as soot and coke) that the state of the art reports and was calibrated based on industrial data and with the predicted concentration profile of benzene. According to the model for the cracking reactor evaluated in this research, the reduction in the diameter is 30% higher when the raw material of the reactor changes from ethane to a mixture of 50%ethane/50%propane